El género Anastrepha (Diptera; Tephritidae) en las principales frutas de Costa Rica y su relación con pseudomiasis humana - Jirón, Luis Fernando (1979)
Three species of Anastrepha are usually found independently in 9 fruits from different regions of Costa Rica. A. striata was found in 5, and A. serpentina and A. obliqua in each of 3 different fruits. During the harvest season, these larvae frequently produce intestinal pseudomyiasis, especially in children.